Initialization Methods for FPGA-Based EMT Simulations - Xin Ma; Xiao-Ping Zhang (IEEE Open Access Journal of Power and Energy)
FPGA has become a very powerful platform to provide real-time Electromagnetic Transient (EMT) solutions due to the much lower investment costs in comparison to the other existing real-time platform. Existing off-line initialization methods cannot be applied to real-time FPGA directly owing to timing constraints and resource utilization. Without appropriate initialization, it can lead to divergence for FPGA-based EMT simulations and cause inaccurate simulation results. To provide real-time initialization, this paper presents four initialization methods for FPGA-based EMT, namely, physical interface (Method 1), signal declaration (Method 2), signal assignment (Method 3) and Coefficient (COE) file (Method 4). The performance of these four methods are also compared, and Method 4 can initialize instantly with the simplest code. To improve hardware adaptability, optimized strategies are developed for address sequence, interface, update modes and dataflow. To accelerate initialization, software-to-hardware algorithm and structure are developed to automate initialization data sources for different topologies. Case study shows Method 2–4 can both initialize successfully on FPGA platform, while Method 4 achieves the best timing and routing performance. To verify scalability, Method 4 is expanded to initialize 4-machine 11-bus system and eliminate significant error to less than 5%, with a timing constraint of 0.005 ns.